2010
DOI: 10.1097/mpa.0b013e3181c72baf
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Pancreatic Cancer Effects of a Polar Extract From the Edible Sea Cucumber, Cucumaria frondosa

Abstract: Frondanol-A5 causes cell cycle arrest and apoptosis in human pancreatic cancer cells. These changes are associated with decreased expression of cyclin A, cyclin B, and cdc25c and increased expression of p21 that, at least in part, is mediated by a p38 kinase-dependent mechanism. Because Frondanol-A5P is derived from an edible, nontoxic, sea cucumber, it may be valuable for nutritional therapy or prevention of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…It has also been demonstrated that Frondanol A5, an impure extract of Cucumaria frondosa skin from which Frondoside A is originally derived, induced growth inhibition at S and G2-M phase with a decrease in Cdc25c and an increase in p21 WAF1/CIP1 with significant apoptosis associated with H2AX phosphorylation and caspase-2 cleavage in the colon cancer-derived HCT116 cells [4]. A second paper also demonstrated that Frondanol-A5P, a polar precipitate sub-fraction of Frondanol-A5, inhibited proliferation and induced G2/M phase cell cycle arrest in two pancreatic cancer cells with decreased expression of cyclin A, cyclin B, and cdc25c [18]. This anticancer effect of Frondoside A is not tissue specific, and in this context we demonstrated that Frondoside A induced a concentration-dependent decrease in cell viability of the melanoma MDA-MB-435, the breast MCF-7, and the hepatoma HepG2 cells.…”
Section: Discussionmentioning
confidence: 89%
“…It has also been demonstrated that Frondanol A5, an impure extract of Cucumaria frondosa skin from which Frondoside A is originally derived, induced growth inhibition at S and G2-M phase with a decrease in Cdc25c and an increase in p21 WAF1/CIP1 with significant apoptosis associated with H2AX phosphorylation and caspase-2 cleavage in the colon cancer-derived HCT116 cells [4]. A second paper also demonstrated that Frondanol-A5P, a polar precipitate sub-fraction of Frondanol-A5, inhibited proliferation and induced G2/M phase cell cycle arrest in two pancreatic cancer cells with decreased expression of cyclin A, cyclin B, and cdc25c [18]. This anticancer effect of Frondoside A is not tissue specific, and in this context we demonstrated that Frondoside A induced a concentration-dependent decrease in cell viability of the melanoma MDA-MB-435, the breast MCF-7, and the hepatoma HepG2 cells.…”
Section: Discussionmentioning
confidence: 89%
“…Recently antitumor activities have been described for crude fractions and isolated single glycosides from sea cucumbers [2-5]. Frondoside A, a triterpenoid glycoside isolated from the sea cucumber Cucumaria frondosa inhibited proliferation and induced apoptosis of pancreatic cancer cell lines as well as growth of human pancreatic and breast cancer xenografts [2,3,5]. A parent compound, Frondanol A5, also inhibited growth of a human colon cancer cell line and, furthermore, prevented primary colon carcinogenesis in a rat model [4].…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor activity of frondoside A and cucumariosides is a result of their activity to induce apoptosis of cancer cells (Li et al, 2008; Jin et al, 2009; Roginsky et al, 2010), including HL-60, NB-4, and THP-1 leukemic cells (Jin et al, 2009). …”
Section: Frondoside a And Cucumariosidesmentioning
confidence: 99%